(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
As the pace of globalization increases, it is becoming more essential for companies to guarantee that they are able to effectively adapt to relevant customer needs and preferences in the countries in which they operate. Excellence in policy development and implementation is essential for both transnational and multinational governments in this regard. This requires constant, customer-focused explanation and confirmation regarding where and when the associated administrations are going, as well as how they may get to their intended prospective roles. As the pace of globalization increases, it is becoming more essential for companies to guarantee that they are able to effectively adapt to relevant customer needs and preferences in the countries in which they operate. Excellence in policy development and implementation is essential for both transnational and multinational governments in this regard. This requires constant, customer-focused explanation and confirmation regarding where and when the associated administrations are going, as well as how they may get to their intended prospective roles.